Employability as an alternative to job security. Issue 1 (4th February 2019) - Bernstrøm, Vilde Hoff; Drange, Ida; Mamelund, Svenn-Erik
Abstract : Purpose: Employability has been suggested as an alternative to job security in response to more flexible work arrangements, arguing that the important question for employees is no longer the security of their current job, but their employment security in the labour market. The purpose of this paper is to test two core assumptions of this argument: first, is employability associated with a lower preference for job security? And second, are individuals with lower job security in fact compensated with higher employability? Both assumptions have received criticism in recent literature. The focus is on employees' perceived basic and aspiring employability. The former refers to employees' expectations of remaining in employment and the latter to expectations of upward mobility. Design/methodology/approach: The data used in the analysis were nationally representative Norwegian survey data from 12, 945 employees (2009–2013). Findings: Employees with higher aspiring employability and education levels have a significantly lower preference for job security, but this is not the case for employees with higher basic employability. Additionally, while employees with lower job security have higher aspiring employability, they have lower basic employability and receive less employer-supported training. Originality/value: The current paper is the first to investigate how employability relates to the employees' own preference for job security. In line with critics of the employability argument, the results support that job security continues to be an important protection mechanism. Moreover, employees with low job security lose out twice as employers also invest less in their training and future employability.